Involvement of the plasminogen activation system in mammalian reproduction - TSANTARLIOTOU (Μ. ΤΣΑΝΤΑΡΛΙΩΤΟΥ) M.; SAPANIDOU (Β.ΣΑΠΑΝΙΔΟΥ) V.; ZERVOS (Ι. ΖΕΡΒΟΣ) I.; LAVRENTIADOU (Σ. ΛΑΥΡΕΝΤΙΑΔΟΥ) S.; TAITZOGLOU (Ι. ΤΑΪΤΖΟΓΛΟΥ) I.; KOKOLIS (Ν. ΚΟΚΟΛΗΣ) N. (Journal of the Hellenic Veterinary Medical Society, 2017)
The current knowledge of the role of local and directed fibrinolysis controlled by plasminogen activators (PAs) and regulated by plasminogen activator inhibitors (PAls) in reproduction is summarized. The PA system has been found to play an important role in spermatogenesis in testis and modulation of sperm maturation in epididymis while a lot of studies indicate a role for sperm or seminal plasma PAs in sperm hyperactivation and/or capacitation. Hormoneinduced expression of tissue-type PA (tPA) and PAI-1 in the ovary is involved in the processes of ovulation and luteal regression; increases of urokinase-type PA (uPA) and PAI-1 in the early stage of luteinized follicles may be responsible for ovarian tissue remodeling and angiogenesis. The targeted proteolytic activity plays an essential role in the processes of the cyclic uterine angiogenesis, implantation and placentation as well as in the parturition. As the PA system is involved in multiple phases of mammalian fertilization specific regulatory molecules of this system provide opportunities for pharmacological intervention.